Nonlinear systems and optimization for the chemical engineer : solving numerical problems - Buzzi-Ferraris, G. (Guido); Manenti, Flavio (Wiley-VCH, 2013)
This third in a suite of four practical guides is an engineer's companion to using numerical methods for the solution of complex mathematical problems. It explains the theory behind current numerical methods and shows in a step-by-step fashion how to use them. The volume focuses on optimization from experimental to large-scale processes, detailing the algorithms needed to solve real-life problems. It describes the methods, innovative techniques and strategies that are all implemented in a well-established, freeware mathematical toolbox called BzzMath, which is developed and maintained by the au.